ACE inhibitors and potassium foods – nurses' knowledge. Issue 1 (4th February 2014) - Bertrand, Brenda; Livingston-Bowen, Carrie; Duffrin, Christopher; Mann, Amanda
Abstract : Purpose: – According to Joint Commission standards, patients should be educated about drug-nutrient interactions. Because nurses are well-suited to educating patients, this paper aims to assess their knowledge of ACE inhibitor drugs, nutrient interactions and high- and low-potassium foods. Design/methodology/approach: – Licensed nurses from a teaching hospital in the US south eastern Atlantic region completed a self-administered questionnaire ( n =83). Means, standard deviations and 95 percent confidence intervals were calculated for continuous data and frequency and percentage distribution for discrete data. Student's t -test was used to evaluate responses by ACE inhibitor patient load and nursing education. Findings: – Mean nurse knowledge of ACE inhibitors and potassium was 62±16 percent and identifying high- and low-potassium foods was 32±23 percent. Most identified five from 12 high-potassium foods and did not know the designation of six, one from 14 low-potassium foods and did not know the designation of 11. Knowledge scores and identifying high- and low-potassium foods were similar regardless of ACE inhibitor patient load and nursing education. Practical implications: – ACE inhibitors are the fourth most commonly used drug class in the USA. Nurses are well positioned to recognize potential drug-nutrient interactions owing to changing or adding a drug, dose delivery method, dietary change or a patient's physical or clinical status that may indicate nutrient deficiency. The findings suggest that the nurses surveyed were proficient in identifying ACE inhibitors pharmacology, but that most were unable to identify foods that increase drug-nutrient interaction risk, and thus this is an area in which additional training might be beneficial. Originality/value: – Case menus were used to portray real-life scenarios in which healthcare practitioners can provide patient education about ACE inhibitor drug and dietary potassium interactions.